Studies Qualitative Thalassemia Selfcare Management Teenagers - Andriani, Ria; Nurhaeni, Nani; Allenidekania, Allenidekania; Ayubi, Dian (Newinera Publisher, 2025)
Study This to study self-care management in adolescents sufferer thalassemia major in the Province West Java, with objective For understand How teenager the manage condition his health is good in a way physique and also psychological. Method research used​ is approach qualitative with design phenomenology, which relies on interview deep against 29 participants aged​ between 10 and 18 years old. The results of the study show that condition physical, complaints physical, results laboratory, and conditions genetics become factor key in the early diagnosis of thalassemia. Support social from family and friends peers also play a role important in increase quality life teenager sufferer thalassemia. Findings This support importance approach holistic in management disease, which includes maintenance medical, education, and support psychosocial For increase ability teenager in manage condition they in a way independent. Programs such as Self-care Management of Adolescent Thalassemia expected can give contribution significant to strengthening self-care among teenager sufferer thalassemia in West Java.